Effects of Swimming in Ice-cold and Warm Water on Changes in Plasma Volume and Free Fatty Acids - Zeman, V.; Holecek, V.; Novàk, J. (Biomechanics and Medicine in Swimming, 1983)
In the CSSR during recent years a special sport has been developing called "sports hardening" or winter swimming. It implies year-round outdoor swimming. During competition the athletes swim, depending on their degree of hardening and swimming fitness, 100-, 250-, 500-, 750-and 1,000-m races in water at temperatures of 0-8°C. The longest time permitted in water is 20 min. We were interested in the rganism's response to this substantial cold stress and compared it with responses to swimming in warm water in a pool.